On the Machine Tool Substitutive Model Creation, Supported by the Finite Element Method - Kaliński, K.J.; Kucharski, T. (Engineering Transactions, 1999)
A primary model is created by the rigid finite element method. The selected "rigid" part which is supposed to be flexible, is idealised by classic finite elements of various kinds. The solution to dynamics of the model introduced is a pattern which the primary model should follow. Suitable accuracy criteria are included to compare the results. If the chosen criterion is satisfied, flexibility of that "rigid' part will be distributed over some spring-damping element. If the latter is not accomplished, the "rigid" part will be subdivided into two rigid finite elements, connected by additional spring-damping element. Some illustrative examples are included.